Crust [videorecording (DVD)] - Wald, Jim; Whalen, Sean, 1964-; Whalen, Sean, 1964-; Josepher, Wendle; Ruck, Alan, 1956- (Anchor Bay Entertainment, 2024)
It tells the story of a lonely laundromat owner, Vegas Winters, who keeps the leftover socks from customers and uses them to clean himself. When he gets abused and weeps into the pile of socks, it turns into a creature who seeks revenge on Vegas' enemies.